Nurturing Self-Learning Strategies at CIEX Language Courses - Brito, Tomás (CIEX JOURNAL, 2018)
This research explores the theoretical foundations to learning issues which influence students and/or serve as guidelines for decisions about learning. It also explores student’s performances in taking responsibility of their own learning in the context of English language courses at a private language center. Nowadays, it is well known that edition requires a learner-centered approach to maximize learning experiences; and this implies focusing the teaching process on the learners. Student's active involvement in reaching the learning goals is supported by a continuum of ingredients, to say, learning autonomy, motivation, cognition and metacognitive awareness, self-regulation and self-direction, learning styles and strategies, and learning habits, among many others. Therefore, the intention of the research is not only to describe the current status quo of these issues within the research context and the theoretical grounds, but also, based on the research findings and conclusions, to suggest actions to harmonize the learning context, goals, students need with the theory. It is important to clarify that the research is in process, hence, the thesis design is the main content of the paper. The methodology, findings, and conclusions will be presented in farther research articles.